The Research Trend of Big Data in Education and the Impact of Teacher Psychology on Educational Development During COVID-19: A Systematic Review and Future Perspective - Li, Jia; Jiang, Yuhong (Frontiers in Psychology, 2021)
The COVID-19 outbreak, along with post-pandemic impact has prompted Internet Plus education to re-examine numerous facets of technology-oriented academic research, particularly Educational Big Data (EBD). However, the unexpected transition from face-to-face offline education to online lessons has urged teachers to introduce educational technology into teaching practice, which has had an overwhelming impact on teachers' professional and personal lives. The aim of this present work is to fathom which research foci construct EBD in a comprehensive manner and how positive psychological indicators function in the technostress suffered by less agentic teachers. To this end, CiteSpace 5.7 and VOSviewer were applied to examine a longitudinal study of the literature from Web of Science Core Collection with the objective of uncovering the explicit patterns and knowledge structures in scientific network knowledge maps. Thousand seven hundred and eight articles concerned with educational data that met the criteria were extracted and analyzed. Research spanning 15 years was conducted to reveal that the knowledge base has accumulated dramatically after many governments' initiatives since 2012 with an accelerating annual growth and decreasing geographic imbalance. The review also identified some influential authors and journals whose effects will continue to have future implications. The authors identified several topical foci such as data mining, student performance, learning environment and psychology, learning analytics, and application. More specifically, the authors identified the scientific shift from data mining application to data privacy and educational psychology, from general scan to specific investigation. Among the conclusions, the results highlighted the important integration of educational psychology and technology during critical periods of educational development.